Electrical stimulated GLUT4 signalling attenuates critical illness‐associated muscle wasting. Issue 4 (3rd May 2022) - Addinsall, Alex B.; Cacciani, Nicola; Backéus, Anders; Hedström, Yvette; Shevchenko, Ganna; Bergquist, Jonas; Larsson, Lars
Abstract: Background: Critical illness myopathy (CIM) is a debilitating condition characterized by the preferential loss of the motor protein myosin. CIM is a by‐product of critical care, attributed to impaired recovery, long‐term complications, and mortality. CIM pathophysiology is complex, heterogeneous and remains incompletely understood; however, loss of mechanical stimuli contributes to critical illness‐associated muscle atrophy and weakness. Passive mechanical loading and electrical stimulation (ES) therapies augment muscle mass and function. While having beneficial outcomes, the mechanistic underpinning of these therapies is less known. Therefore, here we aimed to assess the mechanism by which chronic supramaximal ES ameliorates CIM in a unique experimental rat model of critical care. Methods: Rats were subjected to 8 days of critical care conditions entailing deep sedation, controlled mechanical ventilation, and immobilization with and without direct soleus ES. Muscle size and function were assessed at the single cell level. RNAseq and western blotting were employed to understand the mechanisms driving ES muscle outcomes in CIM. Results: Following 8 days of controlled mechanical ventilation and immobilization, soleus muscle mass, myosin : actin ratio, and single muscle fibre maximum force normalized to cross‐sectional area (CSA; specific force) were reduced by 40–50% ( P  < 0.0001). ES significantly reduced the loss of soleus muscle fibre CSA and myosin : actin ratio by approximately 30% ( P  < 0.05) yet failed to effect specific force. RNAseq pathway analysis revealed downregulation of insulin signalling in the soleus muscle following critical care, and GLUT4 trafficking was reduced by 55% leading to an 85% reduction of muscle glycogen content ( P  < 0.01). ES promoted phosphofructokinase and insulin signalling pathways to control levels ( P  < 0.05), consistent with the maintenance of GLUT4 translocation and glycogen levels. AMPK, but not AKT, signalling pathway was stimulated following ES, where the downstream target TBC1D4 increased 3 logFC ( P  = 0.029) and AMPK‐specific P‐TBC1D4 levels were increased approximately two‐fold ( P  = 0.06). Reduction of muscle protein degradation rather than increased synthesis promoted soleus CSA, as ES reduced E3 ubiquitin proteins, Atrogin‐1 ( P  = 0.006) and MuRF1 ( P  = 0.08) by approximately 50%, downstream of AMPK‐FoxO3. Conclusions: ES maintained GLUT4 translocation through increased AMPK‐TBC1D4 signalling leading to improved muscle glucose homeostasis. Soleus CSA and myosin content was promoted through reduced protein degradation via AMPK‐FoxO3 E3 ligases, Atrogin‐1 and MuRF1. These results demonstrate chronic supramaximal ES reduces critical care associated muscle wasting, preserved glucose signalling, and reduced muscle protein degradation in CIM.